2006
DOI: 10.1007/s11417-006-9009-5
|View full text |Cite
|
Sign up to set email alerts
|

Parental and Peer Influences on Adolescent Drug Use in Korea

Abstract: The analysis and findings reported here are from a self-report questionnaire survey of a sample of 1,035 high school students in Pusan, a metropolitan area of South Korea. Multiple regression and path analyses reveal that, for all types of drug behavior among these adolescents, the influence of parental variables was generally less than the influence of the peer variables. Even in South Korean society, where the stability and authority of the family is greater than in American society, peers have a greater inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 98 publications
(113 reference statements)
6
36
2
Order By: Relevance
“…A previous study conducted in South Korea found results consistent with those in the Unites States and other Western societies (Hwang & Akers, 2006). That study, however, had a limitation.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…A previous study conducted in South Korea found results consistent with those in the Unites States and other Western societies (Hwang & Akers, 2006). That study, however, had a limitation.…”
Section: Introductionmentioning
confidence: 58%
“…Consistent with the basic premise of these two theories, a large body of empirical research confirms the significant predictability of parental influence and peer relationship on juvenile substance abuse behavior (Bahr, Hawks, & Wang, 1993;Bahr, Hoffmann, & Yang, 2005;Brown, Mounts, Lamborn, & Steinberg, 1993;Dishion, Andrews, & Crosby, 1995;Dishion, Patterson, Stoolmiller, & Skinner, 1991;Fergusson, Swain-Campbell, & Horwood, 2002;Hwang & Akers, 2006;G. Lee, Akers, & Borg, 2000;Mebly, Conger, Conger, & Lorenz, 1993;Neff & Waite, 2007;Reed & Rountree, 1997;Walden, McGue, Lacono, Burt, & Elkins, 2005;Warr, 1993aWarr, , 1993b.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous studies have consistently reported that peer influences are generally greater than parental or family influences during adolescence (Avenevoli & Merikangas, 2003;Hwang & Akers, 2006;Kobus, 2003). The TTI model also demonstrates that the influence of peers on an adolescent's use of tobacco is greater than that of parents Flay et al, 1999).…”
Section: Discussionmentioning
confidence: 84%
“…One reason for this limitation, according to Gottfredson and Hirschi, is because theirs is a general theory that is not confined to our particular culture and scholars have assumed that there are no differences in how self-control predicts deviance across cultural and national groups. The other reason, which perhaps is more practical and veritable, is because scholars have confronted difficulties in developing measures of theoretical variables in different languages and collecting identical data at the same time in a similar setting across cultures (see also Dussich, Friday, Okada, Yamagami, & Knutden, 2001;Hwang & Akers, 2006).…”
Section: Discussionmentioning
confidence: 99%